2015
DOI: 10.1073/pnas.1501947112
|View full text |Cite
|
Sign up to set email alerts
|

C5orf30 is a negative regulator of tissue damage in rheumatoid arthritis

Abstract: The variant rs26232, in the first intron of the chromosome 5 open reading frame 30 (C5orf30) locus, has recently been associated with both risk of developing rheumatoid arthritis (RA) and severity of tissue damage. The biological activities of human C5orf30 are unknown, and neither the gene nor protein show significant homology to any other characterized human sequences. The C5orf30 gene is present only in vertebrate genomes with a high degree of conservation, implying a central function in these organisms. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…We identified 34 gene pairs (36 unique genes) with significant changes in correlation from the healthy state to disease uninflamed and inflamed states (Supplemental Table 6). Recent studies offer insights into potential roles in IBD-relevant pathways for the proteins encoded by these genes, such as C1ORF106 in autophagy- dependent intracellular pathogen defense (37) and C5ORF30 in negative regulation of immune and inflammatory pathways (38), but the activities of many of the genes remain to be studied in the context of IBD or other immune-mediated diseases.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 34 gene pairs (36 unique genes) with significant changes in correlation from the healthy state to disease uninflamed and inflamed states (Supplemental Table 6). Recent studies offer insights into potential roles in IBD-relevant pathways for the proteins encoded by these genes, such as C1ORF106 in autophagy- dependent intracellular pathogen defense (37) and C5ORF30 in negative regulation of immune and inflammatory pathways (38), but the activities of many of the genes remain to be studied in the context of IBD or other immune-mediated diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, C5orf30 (a methylation biomarker cg17605604) was reported as a damaging regulator of tissue in RA, which is highly expressed in RA synovial fibroblast (RASF) involving joint destruction (Muthana et al, 2015). The clinical data analysis also demonstrated that the variant rs26232 in C5orf30 locus was testified to be associated with RA susceptibility and radiologic damage severity.…”
Section: Biological Observations Of Methylomic Biomarkersmentioning
confidence: 98%
“…Expression of MACIR has been shown to have a significant impact on the immunometabolism of macrophages and fibroblasts in autoimmune conditions. It is highly expressed in the synovium of rheumatoid arthritis patients compared with control synovial tissue where it is predominately expressed by synovial fibroblasts and macrophage and loss of expression contributes to the pathology of inflammatory arthritis in vivo, with inhibition of MACIR in the collagen-induced arthritis model leading to accentuated joint inflammation and tissue damage (1). MACIR expression has been shown to regulate macrophage phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…MACIR, previously named C5orf30, is a negative regulator of tissue damage and 26 inflammation in rheumatoid arthritis (RA). It is highly expressed in the synovium of 27 rheumatoid arthritis patients where it is predominately expressed by fibroblasts and 28 macrophages (1). Reduced MACIR expression is an early event in the pathogenesis of RA 29…”
Section: Introduction 25mentioning
confidence: 99%
See 1 more Smart Citation